Determination of Potassium in Empty Bunches Palm Oil (Elaeis guineensis Jacq.) Using Flame Photometry Method - Alva, Sagir (Talenta Publisher, 2021)
Research on the determination of potassium in empty bunches palm oil have been done with the flame photometry method. The samples were taken randomly from five areas in Northen Sumatera with various heights in the range of < 25- 400 m above sea level. The first sampling was of Datuk Bandar district at Tanjung Balai < 25 m, Meranti district at Kisaran 50 to 100 m, Bosar Maligas district at Simalungun 150-200 m, Simarimbun district at Pematang Siantar 250 to 300 m, and the last Sari Matondang district at Sidamanik 350-400 m. The sample was digested using concentrated nitric aid and 30% hydrogen peroxide then heated with the addition of nitric acid concentrated. Potassium content was measured with a flame photometer at specific 767.5 nm by using calibration methods. The result obtained that potassium contents in the samples were 11.83%; 17.56%; 21.89%; 24.68%, and 25.14% for Tanjung Balai, Kisaran, Simalungun, Pematang Siantar, and Sidamanik respectively. The data obtained showed the higher area of the sea, the lower the temperature so the content of potassium increased in the palm oil empty bunches.